Political Geology Active Stratigraphies and the Making of Life - Bobbette, Adam.; Donovan, Amy.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Palgrave Macmillan, 2019)
This book builds on the enthusiasm for the geological generated by the Anthropocene but expand beyond it in three ways. First, it will probe deeper into the politics, history, and contemporary practices of the geological sciences as a way of thinking, representing, and communicating the geos. This will open up the history of the earth sciences as a science that has been fundamentally imbricated with politics and that its politics has been one of making the geological sensible. Second, it will consider in detail geologies that are volatile and vulnerable and that because of this are subject to practices of governance. Finally, it will multiply the tradition of geological thought in the sciences by considering subaltern, amodern, vernacular, and counter traditions of geological practice and science and its political resonances. This volume will consider these three frameworks through essays historical, ethnographic and conceptual, mindful of the richness of empirical detail and the innovative consequences of looking at the intersections of geology and politics. The book brings together key thinkers on geological politics and political geology as well as emerging topics in human and cultural geography. It will include ten clearly structured chapters, and will seek to solidify a field of inquiry that is of interest to geographers, philosophers of science, anthropologists and sociologists.
Introduction; Adam Bobbette and Amy Donovan -- Part I. Knowing the Geos of Politics -- Chapter 1. Genealogies of Geomorphological Techniques: An STS history; Rachael Tily -- Chapter 2. Hollow Soil: The Politics of Infiltration in Iztapalapa; Seth Denizen -- Chapter 3. Geo-logics and Geo-politics: Knowledge Controversies in Unconventional Fossil Fuels Development; Karg Kama -- Chapter 4. Mining Hashima: Geopower, Differentiated Vitalism and the Violence of Expropriation; Deborah Dixon -- Part II. Amodern Political Geologies -- Chapter 5. Cosmological reason on a volcano; Adam Bobbette -- Chapter 6. Against 'terrenism': Léopold Sédar Senghor, Pierre Teilhard de Chardin and the fear of a de-spiritualised Earth;Angela Last -- Cahpter 7. The Memory of the Earth;Bronislaw Szerszynski -- Part III. Political Geology of the Future -- Chapter 8. Attention in the Anthropocene;Simone Kotva -- Chapter 9. Meetings with Magma: Three Political Geologies; Nigel Clark -- Chapter 10. Explosive Geopolitics and the making of disaster; Amy Donovan -- Epilogue: Problematising the Earth; Amy Donovan.
Keywords: Environment; Physical geography; Environmental sciences -- Social aspects; Geology; Anthropology; Science -- History; Environmental Sciences; Physical Geography; Environmental Social Sciences; Geology; Anthropology; History of Science